1993
DOI: 10.1182/blood.v82.6.1695.bloodjournal8261695
|View full text |Cite
|
Sign up to set email alerts
|

Results of fludarabine and prednisone therapy in 264 patients with chronic lymphocytic leukemia with multivariate analysis-derived prognostic model for response to treatment [see comments]

Abstract: Two hundred sixty-four patients with chronic lymphocytic leukemia were treated with fludarabine 30 mg/m2 intravenously for 30 minutes each day for 5 days and with prednisone 30 mg/m2 orally each day for 5 days. Courses were repeated monthly. Of the 264 patients. 125 patients (47%) had Rai stage III-IV disease; 169 patients (64%) were previously treated with a median of 3 prior regimens; and 138 of them (82%) were refractory to therapy with alkylating agents. The overall response (OR) and complete response (CR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
2
6
1
Order By: Relevance
“…This result is remarkable since FC induced a significantly higher rate of severe leucopenia compared with fludarabine alone. Within previous trials, fludarabine alone resulted in a 4-16% rate of major infections (O'Brien et al, 1993;Johnson et al, 1996;Rai et al, 2000;Leporrier et al, 2001), which is comparable with our results. However, our findings differ from two previous studies that reported a 77% overall infection rate with a 29-34% incidence of severe infections (Anaissie et al, 1998;Morrison et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is remarkable since FC induced a significantly higher rate of severe leucopenia compared with fludarabine alone. Within previous trials, fludarabine alone resulted in a 4-16% rate of major infections (O'Brien et al, 1993;Johnson et al, 1996;Rai et al, 2000;Leporrier et al, 2001), which is comparable with our results. However, our findings differ from two previous studies that reported a 77% overall infection rate with a 29-34% incidence of severe infections (Anaissie et al, 1998;Morrison et al, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…The main infection site in the fludarabine arm was the respiratory tract. This observation has been made in previous trials during fludarabine treatment as well as in CLL patients in general (Molica et al, 1993;O'Brien et al, 1993;Morrison et al, 2001). With FC therapy, FUO was the most prominent cause of infection, which might be related to the higher incidence of severe leucopenia after FC treatment followed by transient bacteremia.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…These investigators reported that expression of p53 protein, as measured by IHC (deemed positive if ‡ 1% of lymphocytes showed 'strong' nuclear staining), was strongly associated with p53 gene mutations, advanced disease, progressive disease, refractoriness to therapy and reduced survival. Univariate analyses of prognostic features in the study population confirmed the importance of b 2 M, prior therapy and Rai stage (O'Brien et al, 1993;Zwiebel & Cheson, 1998). The level of p53 expression joined these established factors as being a significant predictor of survival.…”
Section: Discussionmentioning
confidence: 63%
“…the purine analogues¯udarabine (Hiddemann et al, 1991;Keating et al, 1993;O'Brien et al, 1993;Robertson et al, 1995;Montserrat et al, 1996), deoxycorfomycin (Kefford & Fox, 1982), 2-chlorodeoxyadenosine (2-CDA) (Juliusson et al, 1992) and pentostatin (Dillman et al, 1989) have been introduced into CLL therapeutic strategies. Increasingly, udarabine is being used as initial therapy for patients with CLL Saven et al, 1995;Keating et al, 1998).…”
mentioning
confidence: 99%